Perbandingan Kinerja Keuangan Perusahaan BUMN dan Swasta dalam Bidang Pengelola Jalan Tol - Tamara Latifah Jasmine (MAMEN: Jurnal Manajemen, 2022)
Infrastructure in a country determines economic growth, especially in developing countries. With adequate infrastructure, citizens of a country can get what they need and support all their activities. Infrastructure development itself requires a lot of investment. In Indonesia's Development Plan and Government Work Plan for 2020-2024, it has been explained that the establishment of medium-term needs for infrastructure development in Indonesia amounts to IDR 6,445 trillion. In which, State-Owned Enterprises (SOEs) are estimated to be able to fund only IDR 1,353 trillion or around 21% of the country's total infrastructure funding needs.  In addition, the government also hopes that the private sector can help with the financing amounting to IDR 2,707 trillion or around 42% of the total needs. Toll roads are one of the infrastructures that have grown significantly in Indonesia. In their development, SOEs cooperate with private companies, so that the financing of toll road development is included in the public private partnership (PPP) scheme. This study was conducted with the aim to determine and compare the financial performance between the SOEs which has the longest concession of toll roads in Indonesia, namely PT Jasa Marga (Persero) Tbk. with private parties who also participated in the construction of 5 toll roads in Indonesia, namely PT Citra Marga Nusaphala Persada (CMNP). The data to be used is secondary data from the company's financial statement data. This research uses financial ratio analysis to measure company performance in several aspects, namely in terms of liquidity, solvency, activity, and profitability.